Sitting Time and Cardiometabolic Risk Factors in African American Overweight Women - Rebecca E. Lee; Scherezade K. Mama; Ygnacio Lopez III (Journal of Obesity)
Findings from previous research linking sedentary time with cardiometabolic risk factors and body composition are inconsistent, and few studies address population groups most vulnerable to these compromising conditions. The purpose of this paper was to investigate the relationship of sitting time to cardiometabolic risk factors and body composition among African American women. A subsample of African American women (N=135) completed health and laboratory assessments, including measures of blood pressure, resting heart rate, cholesterol, triglycerides, glucose, body mass index, body fat, sitting time, and demographics. Simultaneous, adjusted regression models found a positive association between weekend sitting time and glucose and an inverse association between weekly sedentary time and cholesterol (ps<.05). There were no significant associations between sedentary behavior and body composition. The unexpected relationship between sedentary time and cholesterol suggests that the relationship of sedentary behavior to cardiometabolic risk factors may depend on existing characteristics of the population and measurement definition of sedentary behavior. Results suggest distinctly different relationships between weekend and weekday sitting time, implicating a need for careful measurement and intervention that reflects these differences.